Contribution to the delineation of Pampa and Atlantic Forest biomes in Santa Maria, RS. - Löbler, Carlos Alberto; Sccoti, Anderson Augusto Volpato; Werlang, Mauro Kumpfer (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Municipality of Santa Maria, RS is located in a transition zone between the Pampa biome and the Atlantic Forest biome. This paper aims to contribute to the delineation of these biomes cartographically. For this information from different sources and scales were used. The information was compiled in the ArcGIS environment where a map of vegetation cover was generated. A cartographic synthesis containing the delimitation of biomes was obtained by superimposing the maps of vegetation cover and map containing elevation of 100 meters. The result showed four classes: occurrence of field 100 m above the level; occurrence of field below the elevation 100 m; occurrence of forest above 100 m elevation, occurrence of forest below 100m elevation. It is concluded that the occurrence of the field below the elevation 100 m characterizes the Pampa biome, and the occurrence of forest above 100 m elevation, defines the Atlantic Forest biome. However, the occurrence of field 100 m above the elevation as well as the occurrence of forest below 100 m elevation, characterized enclaves of these biomes.